Temporal variation in the water quality of ponds and effluent of grow-out ponds of Amazon River prawn Macrobrachium amazonicum - Keppeler, Erlei Cassiano (2012)
This study was conducted in the Crustacean Sector of the Aquaculture Center (CAUNESP) at the São Paulo State University, Jaboticabal (21 ° 15’22”S and 48 ° 18’48”W) São Paulo, Brazil, from December 2003 to May 2004. The aim was to examine the water quality parameters of importance to freshwater prawn culture, operated in a semi-intensive system in Amazon River. Nine 0.01-ha earthen ponds were stocked with 20 juveniles.m -2 . Prawns were fed commercial diet at a rate of 7 to 9% of biomass until the 14th week. After 145 days of stocking, all ponds were drained and harvested. The following water parameters were determined weekly: dissolved oxygen, oxygen biochemical demand, pH, total alkalinity, electrical conductivity, suspended total solids and turbidity, N-nitrate, N-nitrite, N-nitrogen ammonia, N- total, soluble ortophosphate, total phosphorus, chlorophyll and pheophytin. In the semi-intensive culture system of M. amazonicum, there was no clear pattern of temporal variation in the limnological variables studied. Dissolved oxygen, pH, BOD, ammonia nitrogen and nitrate increased in the afternoon period while, the other variables did not change. In general, water quality is more dependent on the biological processes that occur in the pond than on the characteristics of the renewal water for some variable.